2016
DOI: 10.3917/spub.165.0613
|View full text |Cite
|
Sign up to set email alerts
|

Les facteurs de motivation au travail chez les cadres paramédicaux dans un hôpital tunisien

Abstract: The results of this study will help guide public hospital human resource managers in the choice of measures designed to increase the motivation of their employees in order to ensure staff satisfaction as well as quality health care services..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…This result was markedly different from that of Chekib et al in Tunisia, who found that 65% of the participants in their study had an insufficient level of general motivation (little to no motivation). 2 This difference can be explained by the fact that, in their study, the 1st motivating factor was remuneration, i.e., salary and allowances/bonuses, whereas research has shown that financial incentives were unreliable over time to sustain motivation. 14 We found that collaboration is a much more motivating factor for women than men (p=0.004).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This result was markedly different from that of Chekib et al in Tunisia, who found that 65% of the participants in their study had an insufficient level of general motivation (little to no motivation). 2 This difference can be explained by the fact that, in their study, the 1st motivating factor was remuneration, i.e., salary and allowances/bonuses, whereas research has shown that financial incentives were unreliable over time to sustain motivation. 14 We found that collaboration is a much more motivating factor for women than men (p=0.004).…”
Section: Discussionmentioning
confidence: 92%
“…1 However, this result diverged from several studies which had shown that remuneration was the primary motivating factor for healthcare professionals. [2][3][4][5][6][7][8][9][10][11][12] In this study, remuneration came fourth, which could be explained by low satisfaction with the working environment and the inadequacy of salary about the cost of living, the number of years of training and the workload. 13 Collaboration, which ranked second, was also an important factor in motivating Ouidah District Hospital staff.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Concernant Certaines mesures doivent aussi être entreprises afin de diffuser la culture qualité et la motivation des équipes pour l'accréditation de leurs services. Cette motivation des professionnels constitue la locomotive de toute démarche d'amélioration de la qualité au sein des établissements de santé [20].…”
Section: Discussionunclassified